2018
DOI: 10.3390/medicines5030095
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Lifestyle Myopia in Primary School Children—Results from a Transcontinental Pilot Study Performed in Comparison to Moxibustion

Abstract: Background: Lifestyle risks for myopia are well known and the disease has become a major global public health issue worldwide. There is a relation between reading, writing, and computer work and the development of myopia. Methods: Within this prospective pilot study in 44 patients aged between 6 and 12 years with myopia we compared possible treatment effects of acupuncture or moxibustion. The diopters of the right and left eye were evaluated before and after the two treatment methods. Results: Myopia was impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…To date, there is no published evidence that treatments have any significant effect on myopia control. [25][26][27] Prior to enrolling in ortho-k, 27% of participants in the current study had tried myopia control using these alternative methods, but stopped due to ineffectiveness, high cost and inconvenience.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no published evidence that treatments have any significant effect on myopia control. [25][26][27] Prior to enrolling in ortho-k, 27% of participants in the current study had tried myopia control using these alternative methods, but stopped due to ineffectiveness, high cost and inconvenience.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture-moxibustion is one major part of traditional Chinese medicine (TCM). Acupuncture treatment can produce certain effect in reducing myopia in kids [ 19 ]. Nevertheless, acupuncture requires high operation skills and most children are afraid of needling, which make it difficult for large-scale promotion.…”
Section: Research Backgroundmentioning
confidence: 99%
“…[ 24 , 25 ] In addition, some randomized controlled trials (RCTs) have reported that acupuncture, as an adjuvant therapy, can effectively improve the diopter and vision in the sense of myopic children. [ 26 , 27 ] Deqi is considered to be an important parameter to achieve curative effect in acupuncture treatment in traditional Chinese medicine theory and practice. [ 28 ] Deqi is a complex cluster of sensation evoked by acupuncture stimulation, including aching, dull, heavy, numb, radiating, spreading, and tingling.…”
Section: Introductionmentioning
confidence: 99%